INCREASING EFFICIENCY OF FOREIGN-LANGUAGE TEACHING: GAMIFICATION TECHNOLOGIES IN EDUCATION - Dugalich, Natalia; Alontseva, Natalia; Vasilieva, Yulia; Rubannikova, Irina; Mikheeva, Maria; Kudryashova, Nina (Revista Inclusiones, 2020)
One of the issues related to teaching a foreign language is student involvement in the learning process. In the modern technological world, the teacher needs to expand their methodological toolbox by adding the latest methodological discoveries to modernize the classical model of a practical lesson. In view of this, the transfer of gaming elements into the non-gaming environment of teaching a foreign language can improve the results of learning. The article deals with the process of gamification as a promising innovative means of improving the foreign-language competence of college-level students in the process of teaching foreign languages. An analysis of academic literature on the implementation of gamification into the educational process has been carried out. Based on an expert survey, the authors have determined the key technologies of game-based educational activity adopted in foreign language teaching, the connection between these technologies and information technology use and the acceptability of certain technologies of game-based educational activity depending on the type of a higher education institution.